Les mécanismes de sollicitation à la demande d'aide privilégiés par les étudiants du postsecondaire - Nicole Racette; Louise Sauvé; Normand Bourgault; Denise Berthiaume; Marie-Michèle Roy (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Following a study conducted with students who encounter difficulties (n=417) as well as students who have been diagnosed with a learning disability (n=42), we are presenting the marketing mechanisms that are of interest to students in terms of raising awareness of the help available to them as well as the mechanisms that encourage them to seek help. The 459 post-secondary students evaluated 28 marketing mechanisms for getting help. Use of email and the institutions’ Website are the favoured mechanisms for finding out what help is available and for encouraging students to seek help. College students demonstrated a significant preference for interpersonal (one on one) mechanisms while university students favored technology-based mechanisms (p < .05). Only 49,1 % of students who frequently encounter difficulties but do not have a learning disability access help, whereas 75,8 % of students with learning disabilities access help.